Self-supporting covalent organic framework membrane based on water buffer interfacial polymerization as well as preparation method and application of self-supporting covalent organic framework membrane

The self-supported covalent organic frame film is prepared by a method based on water buffer interface polymerization, which solves the problems of zinc metal corrosion and dendrite growth in aqueous zinc ion batteries, and achieves efficient zinc ion deposition and battery performance improvement.

CN119143954APending Publication Date: 2024-12-17SOUTHEAST UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411247152.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The corrosion of zinc metal and dendrites and dendrites in existing aqueous zinc-ion batteries leads to low Coulomb efficiency, limited life and low energy density, and the ion regulation functionality of glass fiber membranes is insufficient, resulting in zinc negative electrode corrosion and dendrites growth.

Method used

Using a self-supported covalent organic frame film based on water buffer interface polymerization, the acetic acid solution with porous polymerization is formed by adding deionized water to the organic solution containing aldehyde-based monomers. A self-supported covalent organic frame film of partial and dense layers, providing ion selectivity and uniform transport functions.

Benefits of technology

The covalent organic frame separator with high mechanical strength and ion sieving performance has been achieved, which significantly improves the number of zinc ion migrations, reduces the surface side reactions of zinc negative electrodes, improves the coulomb efficiency and cycle life of the battery, and reduces the battery cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143954A_ABST
    Figure CN119143954A_ABST
Patent Text Reader

Abstract

The invention discloses a self-supporting covalent organic framework membrane based on water buffer interfacial polymerization and a preparation method and application thereof.The preparation method of the self-supporting covalent organic framework membrane based on water buffer interfacial polymerization comprises the following steps that 1, deionized water is added into an organic solution containing an aldehyde group monomer to serve as a water buffer layer, and freezing is conducted; 2, adding an acetic acid solution containing an amino monomer to the water buffer layer obtained in the step 1 from the upper part of the water buffer layer; and 3, standing at room temperature for reaction, and polymerizing at an oil-water interface to form the uniform self-supporting covalent organic framework membrane. The preparation method can be used for preparing the large-area self-supporting covalent organic framework membrane, and the prepared covalent organic framework membrane has the advantages of no defect, ultrathin thickness and high mechanical strength; the obtained covalent organic framework film has a unique porous layer and compact layer structure, so that the good mechanical strength, electrolyte filling performance and ion function screening performance of the covalent organic framework film are ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an organic framework membrane and a preparation method and application thereof, in particular to a self-supporting covalent organic framework membrane based on water buffered interfacial polymerization and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries face problems such as safety and material shortages, while aqueous batteries are expected to become a substitute for lithium-ion batteries due to their advantages such as low cost, inherent safety, environmental protection and simple process. Aqueous zinc-ion batteries have become one of the candidates for the next generation of large-scale energy storage systems due to their low cost, high safety and excellent rate performance. However, the current problems of corrosion, hydrogen evolution and uncontrollable dendrite growth on the zinc metal negative electrode are the key factors leading to the low Coulombic efficiency, limited life and low energy density of aqueous zinc-ion batteries. In order to solve these thorny problems, researchers have developed a variety of methods for stabilizing the zinc metal negative electrode, including optimizing the electrolyte composition, designing gel electrolytes, constructing zinc negative electrode protective layers and modifying the diaphragm functional layers. However, the above methods cannot fundamentally solve the problem, and often increase the battery cost and reduce the energy density of the battery accordingly.

[0003] At its root, the occurrence of zinc metal corrosion and dendrite growth originate from the non-uniform deposition dynamics of zinc ions. A more scientific approach is to design a new type of diaphragm with a unique structure and ion selective transport capability. The diaphragm is an important component in the battery system, which has a significant impact on the cost, life, performance and safety of the battery. To date, the most reported aqueous zinc-ion battery diaphragm is the glass fiber membrane. The high density and thickness (about 300 microns) of the glass fiber membrane significantly reduce the energy density of the aqueous zinc-ion battery. The thickness reduces the volume energy density. More importantly, the glass fiber membrane does not have the functionality of ion regulation, which will lead to corrosion and dendrite growth on the zinc negative electrode side. The development of a lightweight, ultra-thin diaphragm with selective screening capabilities to achieve uniform zinc ion deposition and inhibit zinc dendrites is urgently needed for the development of aqueous zinc-ion batteries.

[0004] It is worth noting that covalent organic frameworks have one-dimensional ordered mesoporous channels and have been widely used in gas separation, gas storage and catalysis. Among them, covalent organic frameworks connected by hydrazone bonds have excellent hydrolytic stability and functional properties. However, due to the difficulty in preparing large-area independent self-supporting covalent organic framework membranes and their poor mechanical properties, there has been no report on the direct use of covalent organic framework membranes as battery separators. Summary of the invention

[0005] Purpose of the invention: In order to overcome the deficiencies in the prior art, the purpose of the present invention is to provide a method for preparing a self-supporting covalent organic framework membrane based on water-buffered interfacial polymerization with good ion selectivity and uniform transmission. Another purpose of the present invention is to provide a self-supporting covalent organic framework membrane based on water-buffered interfacial polymerization with high discharge specific capacity and good cycle stability. Another purpose of the present invention is to provide an application of a self-supporting covalent organic framework membrane based on water-buffered interfacial polymerization in an aqueous zinc ion battery separator.

[0006] Technical solution: The method for preparing a self-supporting covalent organic framework membrane based on water buffered interfacial polymerization described in the present invention comprises the following steps:

[0007] Step 1, adding deionized water as a water buffer layer to an organic solution containing an aldehyde monomer, and freezing;

[0008] Step 2, adding an acetic acid solution containing an amino monomer onto the water buffer layer obtained in step 1 from above the water buffer layer;

[0009] Step 3: Allow the reaction to stand at room temperature and polymerize at the oil-water interface to form a uniform self-supporting covalent organic framework membrane.

[0010] Further, in step 1, the aldehyde-containing monomer is terephthalaldehyde, 2,5-dihydroxy-1,4-phthalaldehyde, 2,5-dimethoxy-1,4-phthalaldehyde, trimesic acid, 2-hydroxy-1,3,5-benzenetricarboxaldehyde, 2,4-dihydroxy-1,3,5-benzenetricarboxaldehyde, 2,4,6-trihydroxy-1,3,5-benzenetricarboxaldehyde, 1,3,5-tris(4-formylphenyl)benzene, 1,1':4',1"-terphenyl-3,3",5,5"-tetracarboxaldehyde. One or more. The organic solution is one or more of dichloromethane and chloroform. The concentration of the aldehyde-containing monomer is 0.01 to 1 mmol / 100 mL. The volume of deionized water is 1 to 5 times the volume of the organic solution, and the temperature after freezing is 0 to 25°C. Preferably, the volume of deionized water is 1 times the volume of the organic solution, and the temperature after freezing is 10°C. Taking into account the molecular weight of the aldehyde-containing monomer, the minimization of the pore size after polymerization and the crystallinity of the film, the aldehyde-containing monomer is preferably a trimesic acid monomer.

[0011] Furthermore, in step 1, the organic solution containing the aldehyde group monomer is stirred and ultrasonically subjected to 1 to 10 minutes before use to achieve complete dissolution of the aldehyde group monomer.

[0012] Further, in step 2, the amino-containing monomer is any one of hydrazine monohydrochloride, dihydrazine p-dibenzoate, 2,5-dimethoxybenzene-1,4-di(formyl hydrazide), 2,5-diethoxybenzene-1,4-di(formyl hydrazide), 2,5-dipropoxybenzene-1,4-di(formyl hydrazide), 1,3,5-tribenzoic acid dihydrazide, and 4,4',4",4"'-(porphyrin-5,10,15,20-tetrayl)tetra(benzoyl hydrazide). The molar ratio of the amino-containing monomer to the aldehyde-containing monomer is 0.5 to 2.0. The acetic acid solution of the amino-containing monomer is added by spraying or dripping. Considering the molecular weight of the amine-containing monomer, the minimization of the pore size after polymerization, and the crystallinity of the film, the amino-containing monomer is preferably a 2,5-diethoxybenzene-1,4-di(formyl hydrazide) monomer.

[0013] Furthermore, in step 2, the acetic acid solution containing the amino group monomer is stirred and ultrasonically applied for 5 to 20 minutes to achieve complete dissolution of the amino group monomer in the acetic acid solution.

[0014] Furthermore, in step three, the temperature of the static reaction is 0 to 25° C., and the time is 1 to 10 days.

[0015] Furthermore, in step three, the self-supporting covalent organic framework membrane is purified by soaking in dichloromethane and deionized water for 1 to 5 times, each time for 1 to 24 hours, to remove impurities such as residual monomers and acetic acid.

[0016] The self-supporting covalent organic framework membrane of the present invention comprises a porous part and a dense layer, and has a maximum tensile strength exceeding 0.8 MPa in an electrolyte.

[0017] Application of the self-supporting covalent organic framework membrane described in the present invention in aqueous zinc ion battery separator.

[0018] Furthermore, the coulombic efficiency of the assembled Zn / / Cu battery reached 99.75%, the stable cycle life of the Zn / / Zn symmetric battery reached more than 2200 hours, and the Zn / / MnO 2 The battery has a high discharge specific capacity of 200 mAh / g and a cycle life of 1500 times under 2 A / g conditions.

[0019] Preparation principle: The water-buffered interfacial polymerization method is used to solve the current preparation difficulties of large-area covalent organic framework membranes, and to achieve the controllable preparation of large-area self-supporting covalent organic membranes. The prepared covalent organic framework membrane consists of a porous part and a dense layer, in which the porous part is a porous fiber mesh structure, which improves the mechanical tensile strength and electrolyte filling of the covalent organic framework membrane. The hydrophobically arranged hydrazone-bonded covalent organic framework nanochannels in the dense layer give the membrane the functional characteristics of ion selectivity and uniform transmission due to their negative charge. The removal of active water and salt anions avoids the zinc corrosion and hydrogen evolution reaction in which they participate, and the uniform regulation of the ion concentration avoids the dendrite growth on the surface of zinc metal. In addition, this dual-morphology structure meets the excellent mechanical strength of the covalent organic framework membrane.

[0020] Beneficial effects: Compared with the prior art, the present invention has the following significant features:

[0021] 1. It is capable of preparing large-area self-supporting covalent organic framework membranes, and the prepared covalent organic framework membranes have the advantages of being defect-free, ultra-thin, and having high mechanical strength;

[0022] 2. The obtained covalent organic framework membrane has a unique porous layer and dense layer structure to ensure its good mechanical strength, electrolyte filling and ion functional screening performance;

[0023] 3. The ion function screening property of the obtained covalent organic framework membrane effectively increases the number of zinc ion migration, reduces active water, and reduces the occurrence of side reactions on the zinc negative electrode surface during battery cycling;

[0024] 4. The mechanical properties of the prepared covalent organic framework membrane are significantly improved compared with the traditional glass fiber membrane, and the maximum tensile strength in the electrolyte exceeds 0.8MPa;

[0025] 5. The covalent organic framework separator prepared by the present invention can produce a Zn / / Cu battery with a coulombic efficiency of 99.75%, a stable cycle life of a Zn / / Zn symmetrical battery of more than 2200 hours, and a Zn / / MnO 2 The battery has a high discharge specific capacity of 200 mAh / g and a cycle life of 1500 times under 2 A / g conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Schematic diagram of the structure of the covalent organic framework membrane synthesized in Example 1 of the present invention;

[0027] Figure 2 This is a photo of the covalent organic framework membrane synthesized in Example 1 of the present invention;

[0028] Figure 3 This is a physical picture of water buffered interfacial polymerization in Example 1 of the present invention;

[0029] Figure 4 is a SEM photograph of both sides of the covalent organic framework membrane synthesized in Example 1 of the present invention, wherein a is a dense layer and b is a porous layer;

[0030] Figure 5 Nitrogen adsorption and pore size distribution diagram of the covalent organic framework membrane synthesized in Example 1 of the present invention, (a) nitrogen adsorption diagram, (b) pore size distribution diagram;

[0031] Figure 6 is the infrared spectrum of the covalent organic framework film synthesized in Example 1 of the present invention;

[0032] Figure 7 is the XRD spectrum of the covalent organic framework film synthesized in Example 1 of the present invention;

[0033] Figure 8 is a stress-strain curve of the covalent organic framework film synthesized in Example 1 of the present invention;

[0034] Fig. 9 This is a cycle diagram of a Zn / / Zn symmetric battery of a covalent organic framework separator synthesized in Example 1 of the present invention;

[0035] Fig.10 This is a coulombic efficiency cycle diagram of a Zn / / Cu battery with a covalent organic framework membrane synthesized in Example 1 of the present invention;

[0036] Fig.11 This is a charge and discharge cycle diagram of an aqueous zinc ion battery using a covalent organic framework separator synthesized in Example 1 of the present invention.

[0037] Fig.12 This is a SEM photograph of the zinc negative electrode surface of the Zn / / Zn symmetric battery with the covalent organic framework separator synthesized in Example 1 of the present invention after 1000 cycles. DETAILED DESCRIPTION

[0038] Unless otherwise specified, the materials, reagents, instruments, etc. used in the following examples can be obtained from commercial sources. Experimental methods without specific conditions in the examples are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0039] Example 1

[0040] A method for preparing a self-supporting covalent organic framework membrane based on water buffered interfacial polymerization comprises the following steps:

[0041] (1) Weigh 324 mg (2 mmol) of trimesaldehyde monomer and add it to 2500 mL of dichloromethane solvent. The concentration of the aldehyde-containing monomer is 0.08 mmol / 100 mL. Stir and ultrasonically treat for 5 minutes, and then add it to the bottom of a 40×50 cm rectangular container.

[0042] (2) Measure 2500 mL of deionized water as a water buffer and freeze it to 10 degrees Celsius, then add it to the upper layer of the dichloromethane solution as a water buffer layer;

[0043] (3) Weigh 834 mg (3 mmol) of 2,5-diethoxybenzene-1,4-di(formylhydrazide) monomer and add it to 500 mL of glacial acetic acid solvent, stir and ultrasonicate for 10 minutes to completely dissolve the monomer in the acetic acid solution. Then, the acetic acid solution in which the monomer is dissolved is evenly dripped onto the water buffer layer by spraying. After the above operation is completed, the reaction is allowed to stand at 25°C for 5 days, and a self-supporting covalent organic framework membrane is polymerized at the oil-water interface, such as Figures 1-2 shown.

[0044] (4) The membrane obtained in step (3) was purified by soaking in dichloromethane and deionized water for 3 times, each time for 12 hours, to remove residual monomers and impurities such as acetic acid, and then cut to obtain a covalent organic framework membrane, such as Figures 3-4 As shown. The two sides of the membrane have different morphological results. The upper layer is a dense layer, and the lower layer is a porous layer with interwoven fibers. The porous layer has distributed gaps below 500nm, while the dense layer is tightly packed without gaps. The nitrogen adsorption experiment proves that it has a rich specific surface area and a pore size of about 2 nanometers, such as Figure 5 As shown. Figure 6 As shown in Figure 2, the covalent organic framework membrane has good crystallinity. Figure 7 As shown in the figure, the covalent organic framework membrane contains abundant active functional groups (C=O, NH, C=N), which provides a theoretical basis for the functionalization of subsequent membrane ion screening. In addition, the covalent organic framework membrane has good mechanical tensile strength. 4 ) Under the conditions of infiltration, such as Figure 8 shown.

[0045] Example 2

[0046] A method for preparing a self-supporting covalent organic framework membrane based on water buffered interfacial polymerization comprises the following steps:

[0047] (1) Weigh 420 mg (2 mmol) of 2,4,6-trihydroxy-1,3,5-benzenetricarboxaldehyde monomer and add it to 2500 mL of dichloromethane solvent. The concentration of the aldehyde-containing monomer is 0.08 mmol / 100 mL. Stir and ultrasonically treat for 5 minutes, and then add it to the bottom of a 40×50 cm rectangular container.

[0048] (2) Measure 2500 mL of deionized water as a water buffer and freeze it to 10 degrees Celsius, then add it to the upper layer of the dichloromethane solution as a water buffer layer;

[0049] (3) Weigh 834 mg (3 mmol) of 2,5-diethoxybenzene-1,4-di(formylhydrazide) monomer and add it to 500 mL of glacial acetic acid solvent, stir and ultrasonicate for 10 minutes to completely dissolve the monomer in the acetic acid solution. Then, the acetic acid solution in which the monomer is dissolved is evenly dripped onto the water buffer layer by spraying. After the above operation is completed, the reaction is allowed to stand at 20°C for 3 days, and a self-supporting covalent organic framework membrane is polymerized at the oil-water interface.

[0050] (4) The membrane obtained in step (3) was purified by soaking in dichloromethane and deionized water for 4 times, each time for 18 hours, to remove residual monomers and impurities such as acetic acid, and then cut to obtain a covalent organic framework membrane.

[0051] Example 3

[0052] A method for preparing a self-supporting covalent organic framework membrane based on water buffered interfacial polymerization comprises the following steps:

[0053] (1) Weigh 780 mg (2 mmol) of 1,3,5-tri(4-formylphenyl)benzene monomer and add it to 2500 mL of dichloromethane solvent, where the concentration of the aldehyde-containing monomer is 0.08 mmol / 100 mL. Stir and ultrasonically treat for 5 minutes, and then add it to the bottom of a 40×50 cm rectangular container.

[0054] (2) Measure 2500 mL of deionized water as a water buffer and freeze it to 10 degrees Celsius, then add it to the upper layer of the dichloromethane solution as a water buffer layer;

[0055] (3) Weigh 834 mg (3 mmol) of 2,5-diethoxybenzene-1,4-di(formylhydrazide) monomer and add it to 500 mL of glacial acetic acid solvent, stir and ultrasonicate for 10 minutes to completely dissolve the monomer in the acetic acid solution. Then, the acetic acid solution in which the monomer is dissolved is evenly dripped onto the water buffer layer by spraying. After the above operation is completed, the reaction is allowed to stand at 25°C for 4 days, and a self-supporting covalent organic framework membrane is formed by polymerization at the oil-water interface.

[0056] (4) The membrane obtained in step (3) is purified by soaking in dichloromethane and deionized water twice, each time for 20 hours, to remove residual monomers and impurities such as acetic acid, and then cut to obtain a covalent organic framework membrane.

[0057] Example 4

[0058] A method for preparing a self-supporting covalent organic framework membrane based on water buffered interfacial polymerization comprises the following steps:

[0059] (1) Weigh 34 mg (0.25 mmol) of terephthalaldehyde monomer and add it to 2500 mL of chloroform solvent. The concentration of the aldehyde-containing monomer is 0.01 mmol / 100 mL. Stir and ultrasonically treat for 5 minutes, and then add it to the bottom of a 40×50 cm rectangular container.

[0060] (2) 12500 mL of deionized water was measured as a water buffer and frozen to 0 degrees Celsius, and then added to the upper layer of the dichloromethane solution as a water buffer layer;

[0061] (3) Weigh 8.6 mg (0.125 mmol) of hydrazine monohydrochloride monomer and add it to 500 mL of glacial acetic acid solvent, stir and ultrasonic for 10 minutes to completely dissolve the monomer in the acetic acid solution. Then, the acetic acid solution in which the monomer is dissolved is evenly added dropwise onto the water buffer layer. After the above operations are completed, the reaction is allowed to stand at 0°C for 10 days, and a self-supporting covalent organic framework membrane is polymerized at the oil-water interface.

[0062] (4) The membrane obtained in step (3) is purified by soaking in dichloromethane and deionized water once, respectively, for 24 hours each time, to remove residual monomers and impurities such as acetic acid, and then cut to obtain a covalent organic framework membrane.

[0063] In this embodiment, the terephthalaldehyde monomer in step (1) can be replaced by 2,5-dihydroxy-1,4-benzenedicaldehyde, 2,5-dimethoxy-1,4-benzenedicaldehyde, trimesic acid, 2-hydroxy-1,3,5-benzenetricarboxaldehyde, 2,4-dihydroxy-1,3,5-benzenetricarboxaldehyde, 2,4,6-trihydroxy-1,3,5-benzenetricarboxaldehyde, 1,3,5-tris(4-formylphenyl)benzene or 1,1':4',1"-terphenyl-3,3",5,5 ”-tetracarboxaldehyde monomers. The monohydrochloride hydrazine monomer in step (3) can be replaced by any one of p-dibenzoic acid dihydrazine, 2,5-dimethoxybenzene-1,4-di(formyl hydrazide), 2,5-diethoxybenzene-1,4-di(formyl hydrazide), 2,5-dipropoxybenzene-1,4-di(formyl hydrazide), 1,3,5-tribenzoic acid dihydrazine, 4,4',4",4"'-(porphyrin-5,10,15,20-tetrayl)tetra(benzoyl hydrazide) monomers.

[0064] Example 5

[0065] A method for preparing a self-supporting covalent organic framework membrane based on water buffered interfacial polymerization comprises the following steps:

[0066] (1) Weigh 8558.5 mg (25 mmol) of 1,1':4',1"-terphenyl-3,3",5,5"-tetracarboxaldehyde monomer and add it to 2500 mL of dichloromethane or chloroform solvent, the concentration of aldehyde-containing monomer is 1 mmol / 100 mL, stir and ultrasonicate for 5 minutes, and then add it to the bottom of a 40×50 cm rectangular container.

[0067] (2) 7500 mL of deionized water was measured as a water buffer and frozen to 25 degrees Celsius, and then added to the upper layer of the dichloromethane solution as a water buffer layer;

[0068] (3) Weigh 42345.5 mg (50 mmol) of 4,4',4",4"'-(porphyrin-5,10,15,20-tetrayl)tetrakis(benzoylhydrazide) monomer and add it to 500 mL of glacial acetic acid solvent, stir and ultrasonicate for 10 minutes to completely dissolve the monomer in the acetic acid solution. Then, the acetic acid solution in which the monomer is dissolved is evenly added dropwise onto the water buffer layer. After the above operation is completed, the mixture is allowed to react at 25°C for 1 day, and polymerizes at the oil-water interface to form a self-supporting covalent organic framework membrane.

[0069] (4) The membrane obtained in step (3) was purified by soaking in dichloromethane and deionized water for 5 times, each time for 1 hour, to remove residual monomers and impurities such as acetic acid, and then cut to obtain a covalent organic framework membrane.

[0070] In this embodiment, the 1,1':4',1"-terphenyl-3,3",5,5"-tetracarboxaldehyde monomer in step (1) can be replaced by terephthalaldehyde, 2,5-dihydroxy-1,4-benzenedical, 2,5-dimethoxy-1,4-benzenedical, trimesic acid, 2-hydroxy-1,3,5-benzenetricarboxaldehyde, 2,4-dihydroxy-1,3,5-benzenetricarboxaldehyde, 2,4,6-trihydroxy-1,3,5-benzenetricarboxaldehyde, 1,3,5-tri(4-formyl)-1,3,5-benzenetricarboxaldehyde, The 4,4',4",4"'-(porphyrin-5,10,15,20-tetrayl)tetrakis(benzoic acid hydrazide) monomer in step (3) can be replaced by any one of monohydrazine hydrochloride, p-dibenzoic acid dihydrazide, 2,5-dimethoxybenzene-1,4-di(formyl hydrazide), 2,5-diethoxybenzene-1,4-di(formyl hydrazide), 2,5-dipropoxybenzene-1,4-di(formyl hydrazide), and 1,3,5-tribenzoic acid dihydrazide monomers.

[0071] Application Example 1

[0072] The Zn / / Zn symmetrical battery has zinc foil with a diameter of 10 mm on both sides of the positive and negative electrodes, which is cut into a 12 mm diameter diaphragm material. The covalent organic framework membrane prepared in Example 1 is selected as the diaphragm material, and 2M zinc sulfate electrolyte is used as the electrolyte to assemble into a 2032 button battery.

[0073] like Fig. 9 The cycle diagram of the Zn / / Zn symmetric battery shows that the stable cycle life of the Zn / / Zn symmetric battery reaches more than 2200 hours. The surface morphology of the zinc negative electrode after 1000 cycles is as follows: Fig.10 , the zinc metal surface is smooth without dendrites and corrosion.

[0074] Application Example 2

[0075] The Zn / / Cu battery has a positive electrode of copper foil with a diameter of 10 mm and a negative electrode of zinc foil with a diameter of 10 mm, which is cut into a 12 mm diameter diaphragm material. The covalent organic framework membrane prepared in Example 1 is selected as the electrolyte, and 2M zinc sulfate electrolyte is used as the electrolyte to assemble into a 2032 button cell. Fig.11 This is the coulombic efficiency cycle diagram of the Zn / / Cu battery. It can be seen that the coulombic efficiency reaches 99.75%.

[0076] Application Example 3

[0077] An aqueous secondary zinc ion battery, the positive electrode material of which is MnO 2 (70% MnO 2 Active material, 20% Ketjen black conductive agent, 10% PVDF binder), the negative electrode is zinc foil. The covalent organic framework membrane prepared in Example 1 is selected as the diaphragm material cut into a diameter of 12 mm, and assembled with the positive and negative electrode materials with a diameter of 10 mm to form a 2032 button battery. Under the condition of 2A / g, the aqueous zinc ion battery has a discharge specific capacity of 200mAh / g and a cycle life of 1500 times. Fig.12 It can be seen that Zn / / MnO 2 The battery has a high discharge specific capacity of 200 mAh / g and a cycle life of 1500 times under 2 A / g conditions.

[0078] Comparative Example 1

[0079] The remaining steps of this comparative example are the same as those of Example 1, except that no aqueous buffer solution is added, and the resulting membrane is not uniform. The resulting membrane is made into a Zn / / Zn symmetrical battery according to the preparation method of Application Example 1. The cycling performance of the Zn / / Zn symmetrical battery is tested, and the results show that the battery stability is significantly reduced.

[0080] Comparative Example 2

[0081] The remaining steps of this comparative example are the same as those of Example 1, except that the aqueous buffer solution is not frozen and cooled, and the temperature exceeds the reaction temperature of 25 degrees Celsius. The obtained membrane is made into a Zn / / Cu battery according to the preparation method of Application Example 2. The coulombic efficiency performance is tested, and the results show that the coulombic efficiency is seriously reduced and the cycle life is reduced.

[0082] Comparative Example 3

[0083] The remaining steps of this comparative example are the same as those of Example 1, except that 2500 mL of deionized water is replaced by 500 mL of deionized water. The obtained membrane is prepared according to the preparation method of Application Example 3 to prepare Zn / / MnO 2 The battery was tested for discharge performance and found that the discharge capacity was seriously reduced and the cycle life was shortened.

[0084] Among the above embodiments, the best embodiment is Embodiment 1.

Claims

1. A method for preparing a self-supporting covalent organic framework membrane based on water-buffered interfacial polymerization, characterized in that: The following steps are involved: Step 1, adding deionized water as a water buffer layer to an organic solution containing an aldehyde monomer, and freezing; Step 2, adding an acetic acid solution containing an amino monomer onto the water buffer layer obtained in step 1 from above the water buffer layer; Step 3: Allow the reaction to stand at room temperature and polymerize at the oil-water interface to form a uniform self-supporting covalent organic framework membrane.

2. The method for preparing a self-supporting covalent organic framework membrane based on water-buffered interfacial polymerization according to claim 1, characterized in that: In the step 1, the aldehyde-containing monomer is one or more of terephthalaldehyde, 2,5-dihydroxy-1,4-benzenedical, 2,5-dimethoxy-1,4-benzenedical, trimesic acid, 2-hydroxy-1,3,5-benzenetricarboxaldehyde, 2,4-dihydroxy-1,3,5-benzenetricarboxaldehyde, 2,4,6-trihydroxy-1,3, 5-benzenetricarboxaldehyde, 1,3,5-tris(4-formylphenyl)benzene, and 1,1':4',1''-terphenyl-3,3'',5,5''-tetracarboxaldehyde.

3. The method for preparing a self-supporting covalent organic framework membrane based on water buffered interfacial polymerization according to claim 1, characterized in that: In the step 1, the organic solution is one or more of dichloromethane and chloroform.

4. The method for preparing a self-supporting covalent organic framework membrane based on water-buffered interfacial polymerization according to claim 1, characterized in that: In the step 1, the concentration of the aldehyde-containing monomer is 0.01-1 mmol / 100 mL.

5. The method for preparing a self-supporting covalent organic framework membrane based on water buffered interfacial polymerization according to claim 1, characterized in that: In the step 1, the volume of the deionized water is 1 to 5 times the volume of the organic solution, and the temperature after freezing is 0 to 25°C.

6. The method for preparing a self-supporting covalent organic framework membrane based on water buffered interfacial polymerization according to claim 1, characterized in that: In the step 2, the amine-containing monomer is any one of hydrazine monohydrochloride, dihydrazine p-dibenzoate, 2,5-dimethoxybenzene-1,4-di(formyl hydrazide), 2,5-diethoxybenzene-1,4-di(formyl hydrazide), 2,5-dipropoxybenzene-1,4-di(formyl hydrazide), 1,3,5-tribenzoic acid dihydrazide, and 4,4',4'',4'''-(porphyrin-5,10,15,20-tetrayl)tetrakis(benzoyl hydrazide); and the molar ratio of the amine-containing monomer to the aldehyde-containing monomer is 0.5 to 2.

0.

7. The method for preparing a self-supporting covalent organic framework membrane based on water buffered interfacial polymerization according to claim 1, characterized in that: In the step 2, the acetic acid solution containing the amino monomer is added by spraying or dropping.

8. The method for preparing a self-supporting covalent organic framework membrane based on water buffered interfacial polymerization according to claim 1, characterized in that: In the step 3, the temperature of the static reaction is 0-25° C., and the time is 1-10 days.

9. A self-supporting covalent organic framework membrane obtained by the method for preparing a self-supporting covalent organic framework membrane based on water-buffered interfacial polymerization according to any one of claims 1 to 8.

10. Use of the self-supporting covalent organic framework membrane according to claim 9 in aqueous zinc ion battery separator.